2018
DOI: 10.1111/tct.12960
|View full text |Cite
|
Sign up to set email alerts
|

Discharge summary training curriculum: a novel approach to training medical students how to write effective discharge summaries

Abstract: Background: Resident physicians at teaching hospitals write many discharge summaries (DCSs), but receive little formal training or feedback. Poor DCS quality poses a potential patient safety risk. Methods: We developed a curriculum to train fourth-year medical students (MS4s) how to write DCSs and integrated this curriculum into a transition-to-residency course. An inpatient attending physician (IPA) and non-inpatient physician (coach) used structured tools to assess for the presence of key elements within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Medical student education about discharge documentation was recently investigated. 26 This study found that students felt more prepared and confident in their abilities to write discharge summaries, and that they would alter the way they write discharge summaries when they graduated. To expand on this, a PDSA-designed survey completed by junior doctors at induction found that a minority had any formal discharge summary teaching and felt that teaching would be of benefit to them.…”
Section: Discussionmentioning
confidence: 81%
“…Medical student education about discharge documentation was recently investigated. 26 This study found that students felt more prepared and confident in their abilities to write discharge summaries, and that they would alter the way they write discharge summaries when they graduated. To expand on this, a PDSA-designed survey completed by junior doctors at induction found that a minority had any formal discharge summary teaching and felt that teaching would be of benefit to them.…”
Section: Discussionmentioning
confidence: 81%
“…Students tended to overestimate their achieved performance level in comparison to the rating given by experts. One study that compared expert ratings for one EPA did not show significant differences between entrustment ratings of experts [48].…”
Section: Entrustment Ratings and Summative Assessmentsmentioning
confidence: 96%
“…There was an overall heterogeneity with regard to reported educational outcome measures for EPA-based clinical curricula. Assessment methods included written knowledge-based tests [41,48], a combination of these tests with workplace-based assessments [42], and summative and time-variable entrustment and progression decisions [30]. The articles we found addressed the assessment of EPAs primarily within a clinical rotation.…”
Section: Epa Assessment In Clinical Rotations In Umementioning
confidence: 99%
“…IPPs were also unable to undergo formal training on the use of the evaluation tool; therefore, IPP ratings may be prone to greater variability when compared to advisors. Furthermore, senior internal medicine residents were eligible to provide feedback, and they themselves may not have received formal training on authoring discharge summaries, further contributing to variability [6]. In the future, limiting participating IPPs to supervisory attending physicians and PAs, as well as providing standardized training for IPPs, will help to standardize feedback, although there are many logistical barriers to overcome.…”
Section: Limitationsmentioning
confidence: 99%
“…In physician education, there is limited literature describing efforts to train medical students and/or house staff to write discharge summaries. In our previous work, we found that discharge summaries prepared by fourth-year medical students demonstrated frequent errors and omissions, emphasizing the need for early, standardized education [6]. Published curricula have been feasible to implement and improved trainees' competence; however, programs have struggled with sustainability and delivery of personalized feedback [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%